On the independence of assets and liabilities: Evidence from U.S. commercial banks, 1990–2005 - DeYoung, Robert; Yom, Chiwon (Journal of Financial Stability, 2008)
Traditional asset–liability management techniques limit banks’ abilities to structure their balance sheets—but more recently, financial innovations have allowed banks the chance to manage interest rate risk without constraining their asset–liability choices. Using canonical correlation analysis, we examine how the relationships between asset and liability accounts at U.S. commercial banks changed between 1990 and 2005. Importantly, we show that asset–liability linkages are weaker for banks that are intensive users of risk-mitigation strategies such as interest rate swaps and adjustable loans. Perhaps surprisingly, we find that asset–liability linkages are stronger at large banks than at small banks, although these size-based differences have diminished over time, both because of increased asset–liability linkages at small banks and decreased linkages at large banks.